PEMANFAATAN FLY ASH SEBAGAI PENGGANTI SEBAGIAN SEMEN PORTLAND UNTUK MENGURANGI EMISI KARBON - Agus Karmadi, Ketut; Widyasari, Ni Luh (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2024)
Understanding concrete is the most building material in construction industry. Advantages concrete of compared to other materials are that it requires little maintenance fire and water resistant. This study aims to 1) Determine the utilization fly ash from Asphalt Mixing Plan (AMP) in PT. Harapan Jaya Beton for concrete mix; 2) Determine the efficiency percentage of optimal fly ash use in concrete mix. The composition of fly ash used is Portland cement 5%; 10%; 15%; 20%; 30% made from mixture fly ash and Portland I type cement. The results of reaserch showed that burning of AMP as cement component instead of concrete mix. The workability of fly ash at 28 days is 15% with compressive strength of 28.7 MPa and 15% with modulus of elasticity of 14790 MPa. At 56 days the best use is 15% of tensile strength with value of 30.1 MPa and 15% elastic modulus with value of 15325.9 MPa, and at 90 days the best use is 10% compression strength with value of 31.9 MPa and 15% modulus of elasticity with value of 18213.5 MPa. From the above results, it shows that Portland cement can be used by using to reduce carbon emission by 20-30%.